Bone density, microarchitecture, and material strength in chronic kidney disease patients at the time of kidney transplantation - Pérez-Sáez, M; Herrera, S; Prieto-Alhambra, D; Vilaplana, L; Nogués, X; Vera, M; Redondo-Pachón, D; Mir, M; Güerri, R; Crespo, M; Díez-Pérez, A; Pascual, J (Springer London, 2017)
Bone health is assessed by bone mineral density (BMD). Other techniques such as trabecular bone score and microindentation could improve the risk of fracture's estimation. Our chronic kidney disease (CKD) patients presented worse bone health (density, microarchitecture, mechanical properties) than controls. More than BMD should be done to evaluate patients at risk of fracture. INTRODUCTION: BMD measured by dual-energy X-ray absorptiometry (DXA) is used to assess bone health in end-stage renal disease (ESRD) patients. Recently, trabecular bone score (TBS) and microindentation that can measure microarchitectural and mechanical properties of bone have demonstrated better correlation with fractures than DXA in different populations. We aimed to characterize bone health (BMD, TBS, and strength) and calcium/phosphate metabolism in a cohort of 53 ESRD patients undergoing kidney transplantation (KT) and 94 controls with normal renal function. METHODS: Laboratory workout, lumbar spine/hip BMD measurements (using DXA), lumbar spine TBS, and bone strength were carried out. The latter was assessed with an impact microindentation device, standardized as percentage of a reference value, and expressed as bone material strength index (BMSi) units. Multivariable linear regression was used to study differences between cases and controls adjusted by age, gender, and body mass index. RESULTS: Among cases, serum calcium was 9.6 ± 0.7 mg/dl, phosphorus 4.4 ± 1.2 mg/dl, and intact parathyroid hormone 214 pg/ml [102-390]. Fourteen patients (26.4%) had prevalent asymptomatic fractures in spinal X-ray. BMD was significantly lower among ESRD patients compared to controls: lumbar 0.966 ± 0.15 vs 0.982 ± 0.15 (adjusted p = 0.037), total hip 0.852 ± 0.15 vs 0.902 ± 0.13 (adjusted p < 0.001), and femoral neck 0.733 ± 0.15 vs 0.775 ± 0.12 (adjusted p < 0.001), as were TBS (1.20 [1.11-1.30] vs 1.31 [1.19-1.43] (adjusted p < 0.001)) and BMSi (79 [71.8-84.2] vs 82. [77.5-88.9] (adjusted p = 0.005)). CONCLUSIONS: ESRD patients undergoing transplant surgery have damaged bone health parameters (density, microarchitecture, and mechanical properties) despite acceptably controlled hyperparathyroidism. Detecting these abnormalities may assist in identifying patients at high risk of post-transplantation fractures.